PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI PREPP STUDIO JAKARTA - Muhammad Fajar; Trisha Gilang Saraswati (POLITEKNIK LP3I JAKARTA, 2023)
In April 2022 Prepp studio did a 100 Vespa Giveaway which successfully enlivened social media as evidenced by the coverage of well-known media discussing it such as Viva, Wartaekomoni and innews. This study aims to see the effect of the marketing mix on buying interest in Prepp products. This research uses quantitative research methods. The data collection used in this study was a questionnaire distributed to respondents who met the research topic criteria. The sampling technique in this study used nonprobability sampling. Respondents of this study were 100 individuals who knew the products, prices, promotions, location of Prepp Studio and individuals who had purchased Prepp Studio products and also had the desire to buy Prepp Studio products. The results of this study state that the marketing mix variable has a significant effect on the purchase interest variable which has a value of 64.6% so that the authors suggest that the company create a membership card so that consumers who have a member card have a referral code to get points that can be exchanged for discounts for subsequent transactions and provide discounts or cashback for consumers who do testimonials or reviews after transactions so that it will increase trust in potential customers who can increase buying interest in Prepp Studio.Keywords: Marketing mix, Purchase intention and fashion industry.